-10(10n-9)+6(-5n+7)=

Simple and best practice solution for -10(10n-9)+6(-5n+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -10(10n-9)+6(-5n+7)= equation:


Simplifying
-10(10n + -9) + 6(-5n + 7) = 0

Reorder the terms:
-10(-9 + 10n) + 6(-5n + 7) = 0
(-9 * -10 + 10n * -10) + 6(-5n + 7) = 0
(90 + -100n) + 6(-5n + 7) = 0

Reorder the terms:
90 + -100n + 6(7 + -5n) = 0
90 + -100n + (7 * 6 + -5n * 6) = 0
90 + -100n + (42 + -30n) = 0

Reorder the terms:
90 + 42 + -100n + -30n = 0

Combine like terms: 90 + 42 = 132
132 + -100n + -30n = 0

Combine like terms: -100n + -30n = -130n
132 + -130n = 0

Solving
132 + -130n = 0

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-132' to each side of the equation.
132 + -132 + -130n = 0 + -132

Combine like terms: 132 + -132 = 0
0 + -130n = 0 + -132
-130n = 0 + -132

Combine like terms: 0 + -132 = -132
-130n = -132

Divide each side by '-130'.
n = 1.015384615

Simplifying
n = 1.015384615

See similar equations:

| 310=3x-8(8x+7) | | 2(x+1)-1=11 | | c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 | | 7x+6=-12 | | 6a^2+19a+15= | | Y+z=108 | | 8-88n-45n= | | 42=2(x+3)+2(x-12) | | Y=(3x^2-3x+6)*2 | | 2y+3y-5x+2x= | | n+3=q*n | | 42=2(x+3)+(x-12) | | -9(x+2)=16x-3-15x |

Equations solver categories